NON-SYMBIOTIC NITROGEN FIXATION, NET NITROGEN MINERALIZATION AND DENITRIFICATION IN EVERGREEN FORESTS OF CHILOÉ ISLAND, CHILE: A COMPARISON WITH OTHER TEMPERATE FORESTS - Pérez,C.A. (Facultad de Ciencias Naturales y Oceanográficas, Universidad de Concepción, 2003)
Temperate forests in southern Chile offer unique opportunities for studying biogeochemical cycles in the absence of industrial air pollution. Here we compare three important fluxes of the nitrogen (N) cycle in temperate forests of southern Chile, non-symbiotic N fixation, net N mineralization and denitrification, with data from northern temperate forests more affected by air pollution. We studied five evergreen, old-growth forests and one second-growth forest in Chiloé Island, southern Chile. Non-symbiotic N fixation in the litter layer, mineral soil and coarse woody debris was estimated by the acetylene reduction technique. In situ net-N mineralization in the upper mineral soil layer was assessed by the buried bag method. Denitrification rates of mineral soil were assessed by the acetylene inhibition essay in intact soil cores. Results show that in some southern temperate forests a greater proportion of the ecosystem N-fixation occurs in the litter layer (0.23-2.26 kg N ha-1 year-1) and coarse woody debris (1.31-1.34 kg N ha-1 year-1). In contrast, the highest N fixation rates in northern temperate forests occur in mineral soil. Rates of both N mineralization and denitrification were considerably lower in Chiloé forests than in northern temperate forests, which are subject to higher N deposition. These findings suggest that southern temperate forests exert a stronger biotic control on N cycling than their northern counterparts